Pengaruh Media Papan Flanel Terhadap Minat Belajar Siswa - Hadi Gunawan Sakti; Hamzah Parhan (Universitas Pendidikan Mandalika, 2020)
The purpose of this study was to analyze the effect of the use of flannel board media on students' interest in learning mathematics in class VII in Al Rusnaniah Islamic Junior High School. This research method uses experiments. The population in this study was grade VII students of Al Rusnaniah Islamic Middle School. Data collection techniques in this study used a questionnaire and documentation method. Data analysis techniques used statistical analysis with the Chi square formula (〖x〗^ 2). The results of this study indicate that the value of x_ (count) ^ 2 by 6.477 and the value of x_ (table) ^ 2 at a Significant level of 5% with dk (f_h-1) = 2-1 = 1 greater than the value of x ^ 2 in the table (6,477 > 3,841), means that H_0 is rejected and Ha is accepted which reads that there is an influence of the use of flannel board media on students' interest in learning for grade VII in mathematics in Al Rusnaniah Islamic Junior High School, so it can be concluded that the results of this study are significant.